2009
DOI: 10.1007/s10484-009-9089-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intention to Conceal in the P300-based Concealed Information Test

Abstract: The present study examined whether intention to conceal knowledge affects P300 amplitude and detection accuracy in the concealed information test. Eighteen university students were told to choose one card from five and to hide it. In the conceal condition, participants made an effort to leave their chosen card undetected by suppressing their brain response to it. In the transmit condition, they attempted to inform the experimenter of the chosen card by enhancing brain response to it. In the no secret condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 35 publications
3
20
0
1
Order By: Relevance
“…Despite these concerns, this pattern of results regarding awareness is conceptually consistent with many previous ANS-based or ERP-based CIT findings that factors other than memory strength may contribute to the CIT results Elaad & Ben-Shakhar, 1989;Kubo & Nittono, 2009;Meijer et al, 2007;Rosenfeld et al, 2012). We reasoned that as the P300 is elicited by personally significant stimuli, the factors that increase stimulus significance would also increase the corresponding P300 responses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite these concerns, this pattern of results regarding awareness is conceptually consistent with many previous ANS-based or ERP-based CIT findings that factors other than memory strength may contribute to the CIT results Elaad & Ben-Shakhar, 1989;Kubo & Nittono, 2009;Meijer et al, 2007;Rosenfeld et al, 2012). We reasoned that as the P300 is elicited by personally significant stimuli, the factors that increase stimulus significance would also increase the corresponding P300 responses.…”
Section: Discussionsupporting
confidence: 90%
“…It has been found that many of the factors influencing the ANS-based CIT also influence P300-based CITs. For example, when participants have the intention to conceal the probe, larger P300s are elicited than when they have no intention to conceal the information, possibly because the information becomes more salient under the intention-to-conceal condition (Kubo & Nittono, 2009; see also Meijer, Smulders, Merckelbach, & Wolf, 2007). Recently, Rosenfeld, Hu, and Pederson (2012) investigated the effect of deceptive instruction and feedback during a "3-stimulus" P300-CIT (Rosenfeld, 2011), in which on each trial either a probe, irrelevant, or target stimulus is presented.…”
mentioning
confidence: 99%
“…Ferrari et al (2008) found that the positive slow wave (which they referred to as late positive potential) also occurred in response to task-relevant stimuli and reflects the directed attention allocated to task-relevant stimuli. In the CIT, critical items would be significant due to the memorization of the items (Allen and Iacono, 1997;Allen et al, 1992) and task-relevant due to the instruction to conceal critical items (Kubo and Nittono, 2009). The significance and task-relevance of critical items would capture the sustained attention after identifying the critical items, which enhances the positive slow wave.…”
Section: Discussionmentioning
confidence: 99%
“…(The ''lie'' was pushing a ''no'' button as instructed in response to the subject's own name-clearly subjects did not actually intend to deceive the experimenter into believing they did not recognize their own name.) Kubo and Nittono (2009) showed that enhanced P300s in ''deception'' conditions are caused not by a deceptionspecific process but by increased significance due to additional processing.…”
Section: Non-brain Fingerprinting Research On Brainwave-based Concealmentioning
confidence: 99%